(untitled) (Rajarshi Janak University Research Journal, 2025)
Horticulture development is one of the prominent gateways that reduce economic disparity and international trade imbalances; uncertain nutrition and food sovereignty; climatic risks; and unprecedented other problems in the agriculture sector of Nepal. This study aims to identify the gap at the Subtropical Horticulture Development Centre (STHDC), Nuwakot. The analysis reveals the following lead gaps: policy, organizational, managerial, budgetary, communication, productivity, efficiency, profitability, promotion and marketing, product line, distribution, change, and competitive gaps. The results are robust under benefit-cost ratio, SWOT and fishbone techniques. The study is significant against the backdrop of the semi-efficient results of STHDC, increasing fruit imports, and declining agriculture share in GDP.